Antitumor effect of paclitaxel is mediated by inhibition of myeloid-derived suppressor cells and chronic inflammation in the spontaneous melanoma model - Sevko, Alexandra; Michels, Tillmann; Vrohlings, Melissa; Umansky, Ludmila; Beckhove, Philipp; Kato, Masashi; Shurin, Galina V.; Shurin, Michael R.; Umansky, Viktor (The journal of immunology, 2013)
The antitumor effects of paclitaxel are generally attributed to the suppression of microtubule dynamics resulting in defects in cell division. New data demonstrated that in ultralow noncytotoxic concentrations, paclitaxel modulated in immune cells in vitro the activity of small Rho GTPases, the key regulators of intracellular actin dynamics. However, the immunomodulatory properties of paclitaxel in vivo have not been evaluated. In this study, using the ret transgenic murine melanoma model, which mimics human cutaneous melanoma, we tested effects of ultralow noncytotoxic dose paclitaxel on functions of myeloid-derived suppressor cells (MDSCs), chronic inflammatory mediators, and T cell activities in the tumor microenvironment in vivo. Administration of paclitaxel significantly decreased accumulation and immunosuppressive activities of tumor-infiltrating MDSCs without alterations of the bone marrow hematopoiesis. This was associated with the inhibition of p38 MAPK activity, TNF-α and production, and S100A9 expression in MDSCs. The production of mediators of chronic inflammation in the tumor milieu also was diminished. Importantly, reduced tumor burden and increased animal survival upon paclitaxel application was mediated by the restoration of CD8 T cell effector functions. We suggest that the ability of paclitaxel in a noncytotoxic dose to block the immunosuppressive potential of MDSCs in vivo represents a new therapeutic strategy to downregulate immunosuppression and chronic inflammation in the tumor microenvironment for enhancing the efficacy of concomitant anticancer therapies.
Gesehen am 19.08.2021